Distribution of pacific cod Gadus macrocephalus (Gadidae) and functional structure of the habitat in the northern Japan Sea and some issues on regulation of the fishery - А. О. Zolotov (Известия ТИНРО, 2024)
Seasonal and bathymetric distribution of the main age groups of pacific cod in the northern Japan Sea are considered on the data of bottom trawl surveys in 1980–2023. The main wintering and spawning accumulations, where the fish concentrate from December to January and then spawn in February-March, are formed on the external shelf and the upper continental slope along the western coast approximately between Peter the Great Bay and 47о N and along the eastern coast between Cape Krillon and 47о 30′N. The juveniles have feeding migrations from April to May, while older age groups complete the migrations a month later. They migrate in three main directions: from the areas at the mainland coast – southwestward and northeastward and from the areas at western Sakhalin — southward. The juveniles feed on shallows in Peter the Great Bay, northern Tatar Strait, and on southwestern shelf of Sakhalin between the Nevelsky Bay and Cape Krillon, whereas the feeding grounds for older groups occupy two vast areas including Peter the Great Bay with the adjacent southeastern shelf of Primorye and the shelf of northern Primorye in the Tatar Strait (to the north from 47о N) with the whole shelf of Sakhalin. In the northern Tatar Strait (northward from 48о N), the cod belonged to the Primorye and Sakhalin stocks can feed together. The feeding season lasts from June to September. The older cod feed usually deeper that the juveniles. Back migrations of cod for wintering occur from October to November. Because of a joint feeding area where the mainland and Sakhalin stocks are able to mix, the bottom trawl surveys at Primorye coast cannot be used for correct assessment of the total available catch (TAC) in this fishing district. To improve quality of the cod fishery forecasts, the methods of cohort or production analyses should be used, with the control by bottom trawl surveys data, as alternative information about the state of cod stocks, taking into account the abovementioned patterns of seasonal distribution and migrations.